Highly Regioselective Monoacylation of Unprotected Glucopyranoside Using Transient Directing‐Protecting Groups. Issue 3 (23rd January 2017) - Rocheleau, Sylvain; Pottel, Joshua; Huskić, Igor; Moitessier, Nicolas
Abstract : The regioselective functionalization of monosaccharides is notoriously achieved using metal catalysis, lengthy synthetic strategies requiring protection/deprotection, various enzymes, or other methods that target cis ‐diols (and thus cannot be used with glucopyranose derivatives), In this paper, we report a new method using selected boronic acids as temporary protecting groups, and describe its application to the regioselective functionalization of methyl α‐d ‐glucopyranoside, the most difficult monosaccharide to functionalize regioselectively. Generally, reactions of glucopyranosides may lead to a plethora of mono‐ and polyfunctionalized derivatives, yet our method gave the 3‐ O ‐acetylated, 2‐ O ‐benzoylated, and 2‐ O ‐pivaloylated derivatives of methyl α‐d ‐glucopyranoside as major products. We focused on the use of recyclable and green temporary protecting groups (in a one‐pot reaction) and on the modulation of the intramolecular hydrogen‐bonding network using selected arylboronic acids. A complete scalable procedure leading to a single regioisomer from unprotected methyl α‐d ‐glucopyranoside is presented. Abstract : A method for the green, efficient, and highly regioselective functionalization of various glycopyranosides is presented. The method takes advantage of selected boronic acids as temporary protecting groups. Using this approach, a scalable procedure leading to a pure single regioisomer from unprotected methyl α‐d ‐glucopyranoside was developed.